Healthcare 4.0 value creation – The interconnectedness of hybrid value propositions - Aranyossy, Marta; Halmosi, Peter (Technological forecasting & social change, 2024)
Healthcare 4.0, the digital transformation of the healthcare sector through Industry 4.0 technologies, promises to improve patient outcomes, enhance access to healthcare services, improve operational efficiency, empower patients, and even improve the health of nations. This paper contributes to the understanding of the economic and public value creation potential of Healthcare 4.0 technologies. A qualitative content analysis of 21 innovator interviews provides rich data on the value proposition of Healthcare 4.0 technologies for different stakeholders. The findings highlight previously under-researched stakeholder perspectives, the existence of new types of value creation, the relevance of technology in promoting foundational public values and the interconnectedness of the different value elements. •Among other efficiencies Healthcare 4.0 can reduce administrative burdens.•Healthcare 4.0 technologies enable new value-added services to increase revenue.•Collaborative data sharing promises value for multiple stakeholders.•Healthcare 4.0 promotes transparency, reliability, trust and professionalism.•Healthcare 4.0 impacts form an interconnected, interdependent value network.